PENGARUH LABA BERSIH, ARUS KAS OPERASI TERHADAP KEBIJAKAN DEVIDEN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Benge, Fransiska; Djou, Laurentius D Gadi; Londa, Yulita (Program Studi Akuntansi Universitas Flores, 2020)
The research objectives (1) determine the effect of Net Income on Dividend Policy (2) to determine the effect of Operating Cash Flow on Dividend Policy (3) to determine the effect of Net Income and Operating Cash Flow on Dividend Policy. The research sample is 45 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2016 period. Classic assumption test: normality test, autocorrelation test, multicolonierity test and heteroscedasticity test. The data analysis technique used simple regression analysis techniques and multiple regression analysis. The results of the study: (1) Partially Net Profit has a negative effect on Dividend Policy (2) Operational Cash Flow has a negative effect partially and on Dividend Policy (3) Net Income and Operating Cash Flow simultaneously have a negative effect on Dividend Policy.